Subtle interactions for distress regulation: Efficiency of a haptic wearable according to personality. Issue 168 (December 2022) - Béquet, Adolphe J.; Hidalgo-Muñoz, Antonio R.; Moreau, Fabien; Quick, Joshua; Jallais, Christophe
Highlights: Haptic biofeedback wearable (BF) is employed to regulate stress. BF interaction can be modulated in real time during peripheral monitoring contexts. Lower heart rate BF achieves to reduce subjective stress feeling. Levels of neuroticism and extraversion modulates the subjective effect of BF. Studies on stress should consider its multidimensional aspect to measure it. Abstract: The incorporation of empathic systems in everyday life draws a lot of attention from society. Specifically, the use of wearables to perform stress regulation is a growing field of research. Among techniques explored, the haptic emulation of lowered physiological signals has been suggested to be promising. However, some discrepancies remain in empirical research focusing on such biofeedback (BF) regarding their efficacy, and the mechanisms underlying the effects of these wearables remains unclear. Moreover, the influence of individual traits on the efficiency of BF has been marginally studied, while it has been shown that personality could impact both stress and its regulation. The aim of this study is to investigate the outcome of interactions with these technologies from a psycho-physiological standpoint, but also to explore whether personality may influence its efficiency when other interaction devices are present. Participants had to play a challenging game while a lowered haptic BF of their heart rate was induced on their wrist. Results showed variable efficiency of the wearable among the participants: a subjective relaxation was evident for the participants exhibiting the highest neurotic and extraverted traits score. Our results highlight the plurality of the modes of action of these techniques, depending on the individual and on the level of stress to regulate. This study also suggests that tailoring these regulation methods to individual characteristics, such as personality traits, is important to consider, and proposes perspectives regarding the investigation of stress and regulation systems embedded in wearables.